If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + 2) + -1x = 8x + -8 Reorder the terms: 4(2 + 3x) + -1x = 8x + -8 (2 * 4 + 3x * 4) + -1x = 8x + -8 (8 + 12x) + -1x = 8x + -8 Combine like terms: 12x + -1x = 11x 8 + 11x = 8x + -8 Reorder the terms: 8 + 11x = -8 + 8x Solving 8 + 11x = -8 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 8 + 11x + -8x = -8 + 8x + -8x Combine like terms: 11x + -8x = 3x 8 + 3x = -8 + 8x + -8x Combine like terms: 8x + -8x = 0 8 + 3x = -8 + 0 8 + 3x = -8 Add '-8' to each side of the equation. 8 + -8 + 3x = -8 + -8 Combine like terms: 8 + -8 = 0 0 + 3x = -8 + -8 3x = -8 + -8 Combine like terms: -8 + -8 = -16 3x = -16 Divide each side by '3'. x = -5.333333333 Simplifying x = -5.333333333
| 7(g-3)+5g= | | 3=4x^(2/5) | | h-6u+7=-29 | | 6=2k-8k | | E(x)=0.0048x^3-0.0054x^2 | | 7(x-6)=5(x+2) | | 6b^2=42b-72 | | 7(8-9x)=0 | | 3x+9-5x+7-2x=20 | | 7y+45=y-3 | | -x+21=x+9 | | a-17=48 | | 3b-3=9 | | (4x+8)-(2x+4)=2x | | 2x+5(5x-1)=-113 | | 10(c-7)=-36 | | 7/9-= | | 5y/9=45 | | (4x+6)-(2x+4)=2x | | 9x(x+9x)= | | -4.5n+3= | | 3y+20=14 | | 12s-24=0 | | 2(y+1)-5=-15 | | 4j-36=0 | | 8-41=40 | | 4k-42=-1 | | 6+4r=2(r-4) | | 4h-42=-18 | | -10.1=w+.3 | | 5x-3=2x+26 | | 7w+3w=40 |